New Aspects of Corpus Luteum Regulation in Physiological and Pathological Conditions: Involvement of Adipokines and Neuropeptides - Ewa Mlyczyńska; Marta Kieżun; Patrycja Kurowska; Monika Dawid; Karolina Pich; Natalia Respekta; Mathilde Daudon; Edyta Rytelewska; Kamil Dobrzyń; Barbara Kamińska; Tadeusz Kamiński; Nina Smolińska; et al. (Cells, 2022)
The corpus luteum is a small gland of great importance because its proper functioning determines not only the appropriate course of the estrous/menstrual cycle and embryo implantation, but also the subsequent maintenance of pregnancy. Among the well-known regulators of luteal tissue functions, increasing attention is focused on the role of neuropeptides and adipose tissue hormones—adipokines. Growing evidence points to the expression of these factors in the corpus luteum of women and different animal species, and their involvement in corpus luteum formation, endocrine function, angiogenesis, cells proliferation, apoptosis, and finally, regression. In the present review, we summarize the current knowledge about the expression and role of adipokines, such as adiponectin, leptin, apelin, vaspin, visfatin, chemerin, and neuropeptides like ghrelin, orexins, kisspeptin, and phoenixin in the physiological regulation of the corpus luteum function, as well as their potential involvement in pathologies affecting the luteal cells that disrupt the estrous cycle.